Diet selection by sheep and goats on Mediterranean heath-woodland range - Bartolomé, J; Franch, J; Plaixats, J; Seligman, N G (JOURNAL OF RANGE MANAGEMENT, 1998)
The study determined the species components of the diets of small ruminants grazing mountain ranges of the Montseny Biosphere Reserve (Catalunya, NE Spain). Three mixed flocks of sheep and goats, led by shepherds, were monitored for a year. Animals grazed a mountain rangeland composed of Qeurcus ilex woodland and Calluna-Erica heathland during the day and were returned to their corrals every night. Diet selection was estimated using fecal analysis. Of the 111 species that were identified, 71 were common to both sheep and goat. Of these, 23 were represented in proportions of more than 1% of the annual diet. Even though goats and sheep grazed together, their diets were significantly different (p < 0.0001), the animal factor accounting for 18% to 60% of the total variation among the main diet components. Variation between seasons was also a major (5% to 56%) highly significant factor, while differences between flocks accounted for a significant, but relatively small part (3% to 10%) of the total variation in diet. The outstanding difference was the avoidance of the tree, Quercus ilex, by the sheep while the goats selected it throughout the year. Sheep selected graminoids throughout the year while goats tended to avoid them. For the rest there.was substantial overlap in species composition between the diet of sheep and goats, especially when analysed over an entire cycle.
Keywords: calluna vulgaris; Erica arborea; fecal analysis; microhistological analysis; Quercus ilex